Pengayaan Materi Pelajaran Fisika Berupa Pelatihan Untuk Guru Dan Siswa Madrasah Aliyah Ikut OSN/KSM Tingkat Kota Situbondo - Muhammad Munif; Musthafa Syukur; Muhammad Hasan Basri (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2019)
Madrasa Science Competition (KSM) is an annual routine agenda organized by the Ministry of Religion. KSM is implemented in three stages, namely the regency / city level, the provincial level and the national level. Each school can send representatives to attend CBOs. In the implementation, not all schools send their representatives to join the KSM. This is due to the fact that most schools are minimal in terms of resources and facilities. This training was implemented at the Aliyah Fathus Salafi Madrasah School, Tanjung Rejo Village, Mangaran Situbondo. In the KSM coaching activity for the school, we approached the provision of KSM physics materials to the students. The approach is an approach to the basic concepts of physics by giving many examples of physical phenomena in everyday life. With this approach, it is easier for students to digest KSM material and problems with more complexity. After the implementation of KSM training, Madrasah Aliyah Fathus Salafi became more confident and encouraged to participate in the district / city level KSM.